Too great to act in solidarity: The negative relationship between collective narcissism and solidarity‐based collective action - Górska, Paulina; Stefaniak, Anna; Malinowska, Katarzyna; Lipowska, Katarzyna; Marchlewska, Marta; Budziszewska, Magdalena; Maciantowicz, Oliwia (European journal of social psychology, 2020)
Three studies examined the association between narcissistic identification with one’s advantaged in‐group and engagement in solidarity‐based collective action. Drawing on theory and past research, a negative effect of collective narcissism on solidarity‐based collective action was expected. A two‐wave longitudinal study (N = 162) found that Polish participants’ narcissistic, but not secure, national identification decreased their willingness to engage in collective action in solidarity with refugees over time. A field study (N = 258) performed during a mass protest against a proposed abortion ban showed that men’s gender‐based collective narcissism was a negative predictor of solidarity‐based engagement (operationalized as protest behavior and collective action intentions) and this effect was mediated by lowered empathy for women. Finally, a web‐based survey (N = 1,992) revealed that heterosexual/cisgender individuals’ collective narcissism was negatively associated with collective action intentions in support of LGBT rights and that this effect was sequentially mediated by increased intergroup anxiety and decreased empathy for LGBT people. Theoretical implications of the present findings, research limitations, and future directions are discussed.